Efeitos de antiplaquetários e estatinas em marcadores inflamatórios após infarto agudo do miocárdio - Coste, Maria Esther Rochael [UNIFESP] (2018)
Objectives: To evaluate the effects of antiplatelet and statin therapies on the interleukin profile in the acute phase of myocardial infarction and after 30 and 180 days. Methods: A prospective, randomized, open label trial with blinded endpoints aimed to compare four arms of therapies: Ticagrelor/Rosuvastatin (TR), Ticagrelor/Simvastatin (TS), Clopidogrel/Rosuvastatin (CR), Clopidogrel/Simvastatin (CS). The inflammatory response was assessed by IL1β, IL4, IL6, IL10, and IL18 concentrations by ELISA. One hundred and thirtyeight patients of both sexes with acute myocardial infarction with ST segment elevation (STEMI) were included and randomized to one of the four groups of treatment in the first 24hours. All patients followed a pharmacoinvasive strategy. Statistical analysis was performed to compare the effects between treatment groups at the baseline and after 30 and 180 days of the acute event. Results: The mean±SD age of the studied population was 56 ± 9 years, and 92 (66%) were male. The concentrations of IL1β, IL6 and IL18 did not show differences between groups of therapies at baseline. There was a decrease in the four arms of therapies for the concentrations of IL1β, IL6, and IL18 during the study followup. However, an increase in the concentrations of IL4 and IL10 was observed after 30 days of STEMI. There was no correlation at baseline, 30 days and 180 days between LDLC and CT levels and interleukins concentrations (except weak correlation with IL4 and IL6 at 180 days), suggesting low correlation between inflammation and lipids. Conclusions: All the strategies were equally associated with favorable changes in the interleukins profile throughout the treatment.